Oral care practice for the ventilated patients in intensive care units: a pilot survey - Swee Leong, Ong; Lam Soh, Kim; Shariff Ghazali, Sazlina; Geok Soh, Kim (2012)
Ventilator-associated pneumonia (VAP) is the most common nosocomial infection in intensive care units (ICUs). One factor causing VAP is aspiration of oral colonisation, which may result from poor oral care practice. Oral care using tooth brushing can prevent formulation of dental plaque that can be a reservoir for microbes causing VAP. Methodology: A cross-sectional survey was conducted among 124 nurses, using a self-administered questionnaire, to determine methods used, frequency, and attitude of nurses toward oral care provided to mechanically ventilated patients in Malaysian ICUs. Results: Methods for oral care and their frequency of use varied between nurses even in the same unit. Cotton with forceps was used by 73.4% of the nurses. Some nurses used forceps and gauze (65%) or spatulas and gauze (36%). Toothbrushes were used by 50.8% of the nurses. Nurses in this hospital reported to have positive attitude toward providing oral care. Conclusions: The survey showed the need to have standardised oral care protocols in ICUs to improve quality of oral care provided to ventilated patients.